A close‐up view of dynamic biomarkers in the setting of COVID‐19: Striking focus on cardiovascular system. Issue 2 (11th December 2021) - Rezabakhsh, Aysa; Sadat‐Ebrahimi, Seyyed‐Reza; Ala, Alireza; Nabavi, Seyed Mohammad; Banach, Maciej; Ghaffari, Samad
Abstract: Based on the recent reports, cardiovascular events encompass a large portion of the mortality caused by the COVID‐19 pandemic, which drawn cardiologists into the management of the admitted ill patients. Given that common laboratory values may provide key insights into the illness caused by the life‐threatening SARS‐CoV‐2 virus, it would be more helpful for screening, clinical management and on‐time therapeutic strategies. Commensurate with these issues, this review article aimed to discuss the dynamic changes of the common laboratory parameters during COVID‐19 and their association with cardiovascular diseases. Besides, the values that changed in the early stage of the disease were considered and monitored during the recovery process. The time required for returning biomarkers to basal levels was also discussed. Finally, of particular interest, we tended to abridge the latest updates regarding the cardiovascular biomarkers as prognostic and diagnostic criteria to determine the severity of COVID‐19.